Optimization of favipiravir microsponges for pulmonary drug delivery - Priyarini Kothamasi, Vaishnavi Bandari, Khairnar Soham Babasaheb, Bhashpitha Naredla, Naseeb Basha Shaik, Prasanthi Domaraju (Journal of Applied Pharmaceutical Science, 2025)
Microsponges are drug delivery systems that improve drug stability and slow the release rate. Favipiravir (antiviral) microsponges are prepared by the emulsion solvent diffusion method using ethyl cellulose and PVA. Optimization was done by using the Box-Behnken design. Favipiravir microsponges were evaluated for physicochemical parameters, nebulization time (11.6–17.28 minutes), aerosol mass output (0.912%–4.337%), aerosol output rate (0.0082–-0.0187 mg/minute), and respirable fraction (0.535%–2.423%). Based on these criteria of maximum percentage yield, maximum entrapment efficiency, and minimum drug release for 8 hours, the solution with desirability of 0.900 was given. The optimized favipiravir microsponge formulation (PMS) was prepared with the composition of ethyl cellulose (372 mg), PVA (248 mg), and speed (1222 RPM) and evaluated, showed percentage yield of (87.16% ± 0.020%), entrapment efficiency (95.14% ± 0.16%), assay (94.69% ± 0.23%) in-vitro drug release within 8 hours (44.043% ± 0.18%). DSC and XRD studies confirmed the amorphous form of the drug and its compatibility with the excipients used. Thermogravimetric analysis studies showed weight loss in the region of 300°C– 400°C, which indicates degradation and differential thermal analysis effects were observed at 650°C–670°C corresponding to recrystallization of dehydrated material. Thermal analysis and stability studies indicate microsponges are stable even at higher temperatures. The Zeta potential of the optimized formulation (+1.04 mv) indicates stability. SEM of the optimized formulation showed a smooth surface and swelling of the microsponges under the twin-stage impinger stage 1 and stage 2. Favipiravir microsponges of particle size 4.394 ± 0.35 μm, with good flow properties and % EE can be targeted to the lungs.
Keywords: Favipiravir, microsponges, influenza, dry powder inhaler, box-Behnken design